Michel Foucault e a medicina: sobre o nascimento da clínica moderna - Branco, Rosele Maria (2018)
This work starts from the death experiences and the encounter with Michel Foucault thoughts, to interrogate the medical discursive practices about the pretension of the construction of a totalizing and hegemonic knowledge about the individuals. This thesis followed two parallel projects: one seeking to understand the descriptions of the book Naissance de la Clinique about modern medicine, denominated by Foucault as clinical medicine; and the other, concerned to contribute with medical formation. It was decided to organize the work following Foucault demarcations about the medical knowledge that are, mainly, in the book L’archéologie du savoir, because they made sense to explain the generalized dispersion of the medical knowledge in our days. References to Foucault biopolitics studies were included, whereas this moment indicates another important theme from the reflection about medicine. It was concluded that the power of the medical knowledge is in the way that it perceives, penetrates and approaches the body, even though its truths might be partial and provisory. Two dialogue directions are proposed to a new medical art, more flexible, critical and fair: one in the discussion of the new layers that can be added to the medical knowledge, and another, in the analysis of the experiences of medical practices